The information technology industrial revolution and its role in building business strategy of global retail - Ellitan, Lena (Jurnal Manajemen Maranatha, 2020)
The need to process the rate of information more and more quickly, forcing companies to continue on innovate in the field of information technology and devices. A large wave flow and information flow must be immediately processed and used by the company to be able to maintain and improve its business performance. This article will focus on the discussion of the success of the giant global retail and how information technology supports its success and existence. Information technology is also the reason why conventional retail is unable to compete with online retail or e-commerce. Information technology is a catalyst for complementary change, which triggers new innovations that complement each other in business processes, such as finding new ways to reach customers, and new ways to communicate with suppliers and consumers. In other words, information technology has helped build the business strategy of global retail players in developing their business strategies. Likewise what happens in the global retail industry, they will continuously evolve to follow developments in Industry 4.0 and Society 5.0. This 4.0-era global retail company is a pioneer that utilizes the industrial revolution and builds its own dynasty in new retail models introduced by the global retail industry.